Acculturation of Mataraman Local Wisdom with Islamic Values: Implications for Social and Economic Development - Toha, Mohamad; Zuana, Muhammad Mujtaba Mitra; Isbahi, Muhammad Baiqun (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
Economic development is often misinterpreted as merely financial growth and infrastructure expansion. However, the real essence of development lies in a multidimensional approach that incorporates social, cultural, and spiritual aspects, particularly within an Islamic context. This study explores the acculturation of Mataraman cultural traditions with Islamic values, focusing on Bersih Desa and Nyadran practices in Mataraman, Indonesia. Employing an ethnographic approach, data were gathered through observations and interviews with local stakeholders. The study examines how these traditions, initially influenced by Hinduism, have evolved to integrate Islamic teachings, thereby fostering community welfare, environmental stewardship, and social harmony. Results reveal that these practices align with Islamic principles of self-development, collective human prosperity, and the earth's stewardship. They demonstrate that local wisdom, when harmonized with religious values, contributes significantly to economic growth, social cohesion, and sustainable development. The findings underscore the importance of cultural preservation and propose that these traditions be promoted as cultural tourism assets, which could further enhance local economies. Future research is recommended to analyze the broader implications of Mataraman wisdom within the maqashid al-shariah framework.